Adoption and Cost-benefit Analysis of Drip Irrigation for Production of High-Value Crops in Pakistan: Drip Irrigation for Production of High Value Crops - Hussain, Abid; Majeed, Sidra; Hassan, Abdul; Khathian, Mohsin Ali; Khan, Muhammad Zahid Ullah; Raza, Irum; Bajkani, Jumo Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Drip irrigation is regarded as one of the highly efficient methods that allow limited water resources to be properly utilized. The study has been conducted to perform the economic analysis of low and high head drip irrigation systems throughout the country based on data from 100 adopters of drip irrigation through a research & development project funded by the International Center for Agricultural Research in the Dry Areas (ICARDA-Pakistan)/United States Department of Agriculture (USDA). A field survey for the study was conducted in the year 2018 in all the provinces of Pakistan. The study revealed that technology is generally adopted by the farmers having diversified income sources and medium-sized land holdings i.e. ranging from 12.5 to 25 acres. System installation cost-shared 11 percent in low-head drip system of the annual production cost of fruits. While, it shared 29, 32, and 27 percent in case of a high-head system for grapes orchards, vegetables in tunnels, and open fields, respectively. Low-head drip irrigation is profitable for dates/ lemon orchards in Khyber Pakhtunkhwa with a benefit-cost ratio (BCR) of 1.27:1.00. It results in considerable profitability for grapes orchards with BCR of 1.73:1.00 and 1.32:100 in Punjab and Balochistan provinces, respectively. The low-head system is also beneficial for mixed fruit orchards in rain-fed Punjab with a BCR of 1.24:1.00. Similarly, for high-head systems, the benefit-cost ratio was the highest for grapes produced in rain-fed Punjab (2.62:1.00), followed by squash-gourd in irrigated Sindh (2.17:1.00) bitter-gourd in rain-fed Punjab (1.50:1.00) and okra in Sindh (1.22:1.00). However, low and high-head systems could not result in considerable returns for farmers in the case of mixed fruits in Balochistan and cucumber production in tunnels in Punjab province during the study year.